Deskripsi Teologis Kejadian 1 sebagai Dasar dan Strategi Penginjilan di Era Pluralisme - Prakoso, Christian Bayu; Kristiyono, Paul; Suseno, Aji (Sekolah Tinggi Teologi Kanaan Nusantara, 2021)
The existence of a pluralistic and pluralistic society makes most people look for ways to be appreciated and recognized. Religious pluralism emerged as the answer to this problem. However, the wrong approach and interpretation of the Bible makes it a threat to Christianity. The truth about everything was created to be the basis for answering the challenge of religious pluralism. By using a qualitative method with a literature study approach, several evangelistic strategies were produced in the Pluralism era based on the concept of creation in Genesis Article 1. Those strategies include the existence of a person who creates everything, a call from darkness to light, and salvation is present on God's own initiative.AbstrakKeberadaan masyarakat yang mejemuk dan plural membuat sebagian besar orang mencari cara untuk dihargai dan diakui. Pluralisme agama muncul sebagai jawaban akan masalah ini. Namun, pendekatan dan penafsiran yang salah terhadap Alkitab membuat hal ini menjadi sebuah ancaman bagi Kekristenan. Kebenaran tentang segala sesuatu diciptakan menjadi landasan untuk menjawab tantangan pluralisme agama. Dengan menggunakan metode kualitatif pendekatan studi literatur maka dihasilkan beberapa strategi penginjilan di era Pluralisme berdasarkan konsep penciptaan dalam Kejadian Pasal 1. Startegi itu diantaranya adalah adanya pribadi yang menciptakan segala sesautu, panggilan dari gelap menuju terang, dan keselamatan hadir atas inisiatif Allah sendiri.